FILTRASI AIR RAWA GAMBUT DENGAN PADUAN PERLIT-SEMEN-KAPUR - Aziz, Hermansyah; Bukasir, Yennie Puspa; Puryanti, Dwi (Universitas Andalas, 2007)
ABSTRACT Peat water purification by filtration with perlite-cement-lime mixtures was preliminary studied. The filtration was realized under static condition without any pressure. From the experimental results obtained that perlite composition in the mixture plays an important role in the filtration processing. Otherwise the some physical properties of perlite-cement-lime mixture was also determined. Key words: peat water, perlite.